Magnetic shielding sheet

By adopting a multi-layer structure in the magnetic shielding sheet, using resins and adhesives with high heat resistance, and magnetic bodies with low magnetostrictive constant λ, the problems of degradation of protection performance and degradation of magnetic shielding function of the existing magnetic shielding sheet when used in a high temperature environment are solved, and stable performance maintenance in a high temperature environment is achieved.

CN119767653APending Publication Date: 2025-04-04PROTERIAL LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411346953.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-03
Filing Date
2024-09-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When the existing magnetic shielding sheet is used in a high temperature environment, the remelting of the thermoplastic resin causes the resin layer to deform, the magnetic layer may peel off, the protective performance is reduced, and the magnetic shielding function is reduced.

Method used

A laminated body structure consisting of a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer and a second resin layer are adopted. The magnetic layer uses a magnetic body with a magnetostrictive constant λ of 30×10−6 or less, and a material with high heat resistance, such as a resin with a melting point or sublimation point of 250°C or more and an adhesive with a melting point of 150°C or more.

Benefits of technology

Even in a high temperature environment of 100°C or above, it is possible to effectively suppress the appearance deterioration of the magnetic shielding sheet and the decrease in magnetic properties, and maintain good magnetic shielding performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005061231410000181
    Figure BDA0005061231410000181
  • Figure BDA0005061231410000201
    Figure BDA0005061231410000201
  • Figure HDA0005061231420000011
    Figure HDA0005061231420000011
Patent Text Reader

Abstract

The present invention provides a magnetic shielding sheet which can suppress the deterioration of appearance and the reduction of magnetic properties even when used in a high temperature environment. The magnetic shielding sheet is a laminated body which has a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer and a second resin layer in sequence, wherein the magnetic layer is a magnetic layer which contains a magnetic body with a magnetostriction constant λ of 30 or less and has a thickness of 8 μm to 25 μm, the first resin layer and the second resin layer are resin layers which contain a resin with a melting point or a sublimation point of 250°C or more and have a thickness of 1 μm to 24 μm, and the first adhesive layer and the second adhesive layer are adhesive layers which contain an adhesive with a melting point of 150°C or more and have a thickness of 1 μm to 10 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a magnetic shielding sheet. Background Art

[0002] A magnetic shielding sheet that can be used as a magnetic shield or electromagnetic wave shield for electronic equipment, etc., uses amorphous materials and nanocrystalline materials as a magnetic thin strip with excellent magnetic properties, that is, a magnetic layer. Nanocrystalline materials suitable for magnetic layers can be obtained, for example, as follows: a molten metal having an alloy composition that can be adjusted to a nanocrystalline structure, such as Fe-Cu-Nb-(Si, B) system, is quenched and formed into a long strip called an amorphous strip, and then adjusted to a nanocrystalline structure by heat treatment. As an example of a nanocrystalline material, a material form in which at least 50% of the structure is composed of fine grains with an average crystal grain size of less than 100nm can be cited.

[0003] The soft magnetic quenched alloy ribbon of the nanocrystalline material subjected to heat treatment has a lower toughness and a tendency to be brittle than before the heat treatment. In particular, if the ribbon is crystallized and adjusted to a nanocrystalline structure by heat treatment, the tendency to be brittle is obvious and the ribbon is prone to breakage during operation.

[0004] When nanocrystalline materials are used for magnetic shielding sheets, alloy strips in a brittle state are used. If stress is applied during processing and use, cracks, notches, etc. will be generated, and the performance as a magnetic layer will be impaired. Therefore, resin is usually pasted on both sides of the soft magnetic alloy strips to make a laminate for use.

[0005] Therefore, a method of obtaining a laminated body by bonding a thermoplastic resin layer to at least one surface of a magnetic layer has been proposed (see Patent Document 1).

[0006] Thermoplastic resins have good processability. For example, by laminating a thermoplastic resin layer and a magnetic layer and heating them, a protective layer for the magnetic layer can be easily formed. In addition to thermoplastic resins, hot-melt adhesives, so-called hot-melt adhesives, double-sided tapes, thermoplastic resin films with single-sided adhesive layers, etc. can also be used for the protection of the magnetic layer.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2007-317769 Summary of the invention

[0010] Technical problem to be solved by the invention

[0011] However, in recent years, the use of magnetic shielding sheets has expanded, and in addition to suppressing magnetic field noise in electronic devices such as smartphones, tablet-type information terminals, and mobile phones, magnetic shielding sheets are also used in electronic circuits in automobiles, etc. When used in automobiles, etc., it is expected to be used in a higher temperature environment, such as an environment of 100°C or above, compared with the previous operating temperature range of -10°C to +80°C.

[0012] At present, from the viewpoint of processability, general-purpose thermoplastic resins, thermoplastic adhesives, etc. have low heat resistance, and when used at high temperatures, for example, at an ambient temperature of 100°C or above, the thermoplastic resin may remelt. If the resin remelts, the resin layer may deform and peel off from the nanocrystalline material as the magnetic layer, and the resin layer itself may be thermally deformed or thermally discolored. The protective performance of the resin layer of the magnetic layer composed of the nanocrystalline material may be reduced, and defects such as cracking and falling off may occur in the magnetic layer, thereby reducing the function as a magnetic shield.

[0013] An object of one embodiment of the present invention is to provide a magnetic shielding sheet capable of suppressing deterioration of appearance and reduction of magnetic properties even when used in a high-temperature environment.

[0014] Technical solutions for solving technical problems

[0015] The specific technical solutions for solving the above-mentioned problems include the following methods.

[0016] <1> A magnetic shielding sheet comprising a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer, and a second resin layer in this order, wherein the magnetic layer comprises a magnetostriction constant λ of 30×10 -6 The first resin layer and the second resin layer are resin layers respectively containing a resin with a melting point or a sublimation point of more than 250°C and a thickness of 1μm to 24μm, and the first adhesive layer and the second adhesive layer are adhesive layers respectively containing an adhesive with a melting point of more than 150°C and a thickness of 1μm to 10μm.

[0017] <2> A magnetic shielding sheet as described in <1>, wherein the magnetic layer is a strip having a width of 30 mm to 500 mm, the widths of the first resin layer, the first adhesive layer, the second adhesive layer and the second resin layer are greater than 300 mm, and a plurality of the magnetic layers are arranged side by side along the long side of the strip on the surface of the first adhesive layer opposite to the side having the first resin layer.

[0018] <3> The magnetic shielding sheet according to <1> or <2>, wherein the total thickness of the laminate is 33 μm to 65 μm.

[0019] <4> The magnetic shielding sheet according to any one of <1> to <3>, wherein the magnetic shielding sheet is in a wound roll shape.

[0020] <5> The magnetic shielding sheet according to any one of <1> to <4>, wherein the magnetic shielding sheet is a magnetic shielding member obtained by punching the laminate into an arbitrary shape.

[0021] <6> A magnetic shielding sheet as described in any one of <1> to <5>, wherein the first adhesive layer and the second adhesive layer contain a thermosetting adhesive, and in at least one of the first resin layer and the second resin layer, the area change rate before and after heating at a temperature at which the thermosetting adhesive is cured is set to A%, and when the thickness of the first resin layer and the second resin layer is set to Bμm, the product of A and B is less than 30%·μm.

[0022] (Measurement method of area change rate)

[0023] According to JIS C 2151:2019 and ASTM DD1204, the resin film constituting the first resin layer and the second resin layer is cut into a size of 100 mm×100 mm to prepare a sample. In a heat treatment furnace, the obtained resin film sample is heated under the conditions of 200°C×10 min or 150°C×30 min according to the curing temperature of the thermosetting adhesive. The heat shrinkage of the resin film in the width direction and the length direction before and after heating is measured by the following method, the area is calculated using the product of the obtained width and length, and the area change rate is measured by the following formula (a).

[0024] Area change rate (%) = absolute value of [area of ​​the resin film before heating - area of ​​the resin film after heating] / area of ​​the resin film before heating ... formula (a)

[0025] -Method for measuring thermal shrinkage-

[0026] (1) The dimensions of the test piece in the width direction and the length direction before heating are measured respectively.

[0027] (2) The test piece is placed in a hot air circulation thermostatic chamber and is hung in a loaded state at a time and temperature corresponding to the conditions of the raw material of the resin film.

[0028] (3) After heating, the test piece is cooled to room temperature, and then the length of the test piece after the heating treatment is measured for the same portion as the test piece before heating measured previously.

[0029] (4) Using the obtained value, the heat shrinkage ratio is calculated according to the following formula (b).

[0030] Thermal shrinkage (dimensional change) (%) = 100 × (Lo-L) / Lo ... formula (b)

[0031] In the formula (b), Lo represents the size of the test piece before the heating test, and L represents the size of the test piece after the heating treatment.

[0032] In the above measurement method, "suspended under load" means a load applied to the resin film so that it is suspended without deformation such as curling. The load may be appropriately adjusted according to the material of the resin film.

[0033] Effects of the Invention

[0034] According to one embodiment of the present invention, there is provided a magnetic shielding sheet capable of suppressing deterioration of appearance and reduction of magnetic characteristics even when used in a high-temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a cross-sectional view schematically showing an example of the magnetic shielding sheet of the present invention.

[0036] Figure 2 This is a cross-sectional view schematically showing an example of a conventional magnetic shielding sheet.

[0037] Figure 3A This is a schematic structural diagram showing an example of the magnetic shielding sheet of the present invention.

[0038] Figure 3B It is a schematic representation Figure 3A The schematic cross-sectional structural diagram of an example of the overlapping portion of the magnetic layers on the line AA of the magnetic shielding sheet of the present invention is shown.

[0039] Figure 3C It is a schematic representation Figure 3A FIG. 2 is a schematic cross-sectional view of another example of the overlapping portion of the magnetic layers on the line AA of the magnetic shielding sheet of the present invention.

[0040] Figure 4 This is a schematic diagram showing an example of a production apparatus suitable for producing the magnetic shielding sheet of the present invention.

[0041] Figure 5A This is a partially enlarged photograph showing the appearance of the magnetic shielding sheet of Example 1 after the heat treatment.

[0042] Figure 5B This is a partially enlarged photograph showing the appearance of the magnetic shielding sheet of Comparative Example 1 after the heat treatment.

[0043] Figure 6 This is a graph showing the relationship between the heating time and the magnetic permeability of the magnetic shielding sheet of Example 1 and the magnetic shielding sheet of Comparative Example 1 in a high-temperature storage test.

[0044] Figure 7 This is a graph showing the magnetic permeabilities of the magnetic shielding sheet of Example 1 and the magnetic shielding sheet of Comparative Example 1 at frequencies of 100 Hz and 10,000 Hz.

[0045] Figure 8 This is a graph showing the magnetic permeabilities of the magnetic shielding sheet of Example 2 and the magnetic shielding sheet of Comparative Example 2 at frequencies of 100 Hz and 10,000 Hz.

[0046] Fig. 9 This is a graph showing the relationship between the product of the thickness of the first resin layer and the area change rate of the resin layer before and after the heat treatment and the magnetic permeability of the magnetic shielding sheet laminate having the same layer structure as Example 1.

[0047] Description of Reference Numerals

[0048] 1: Resin film roller; 2: Heating roller; 3: Alloy strip roller; 4: Magnetic layer (amorphous alloy strip); 5: Winding machine; 6: Resin layer (resin film); 7: Alloy strip ring; 8: Pressing roller; 9: Magnetic shielding sheet; 10: Magnetic shielding sheet; 12: First resin layer; 14: First adhesive layer; 16: Magnetic layer; 18: Second adhesive layer; 20: Second resin layer; 22: Magnetic shielding sheet; 24: First resin layer; 26: First adhesive layer; 28: Magnetic layer; 30: Second adhesive layer; 32: Second resin layer. DETAILED DESCRIPTION

[0049] Hereinafter, embodiments of the present invention will be described in detail. The present invention is not limited to the following embodiments at all, and can be implemented with appropriate modifications within the scope of the purpose of the present invention.

[0050] When describing the embodiments of the present invention with reference to the accompanying drawings, descriptions of components and reference numerals that are repeated in the drawings are sometimes omitted. Components represented by the same reference numerals in the drawings refer to the same components. The ratios of dimensions in the drawings do not necessarily represent the ratios of actual dimensions.

[0051] In the present invention, the numerical range represented by "~" represents a range including the numerical values ​​recorded before and after "~" as the lower limit and the upper limit, respectively. In the numerical range recorded in stages in the present invention, the upper limit or lower limit recorded in a certain numerical range can also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present invention, the upper limit or lower limit recorded in a certain numerical range can also be replaced by the value shown in the embodiment.

[0052] In the present invention, ordinal numbers (eg, “first” and “second”) are terms used to distinguish between constituent elements, and do not limit the number of constituent elements or the superiority or inferiority of constituent elements.

[0053] In the present invention, the term "process" refers not only to an independent process but also to a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.

[0054] In the present invention, a combination of two or more preferred aspects is a more preferred aspect.

[0055] In the present invention, the magnetic shielding sheet has a sheet-like form. When the surface of the magnetic shielding sheet is rectangular, the short side is defined as "width" and the long side is defined as "length".

[0056] When the magnetic shielding sheet is wound into a roll, the winding direction is defined as a “longitudinal direction”, and the direction perpendicular to the longitudinal direction is defined as a “width direction”.

[0057] When the magnetic layer, adhesive layer, and resin layer constituting the magnetic shielding sheet have a strip-shaped form in which the long side of the sheet is five or more times longer than the short side, the sheet may be referred to as a "strip body".

[0058] The magnetic shielding sheet of the present invention is a laminated body which comprises a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer and a second resin layer in sequence, wherein the magnetic layer is a magnetic layer which contains a magnetic body having a magnetostriction constant λ of less than 30 and has a thickness of 8 μm to 25 μm, the first resin layer and the second resin layer are resin layers which contain a resin having a melting point or a sublimation point of more than 250°C and have a thickness of 1 μm to 24 μm, respectively, and the first adhesive layer and the second adhesive layer are adhesive layers which contain an adhesive having a melting point of more than 150°C and have a thickness of 1 μm to 10 μm, respectively.

[0059] The magnetic shielding sheet of the present invention has a structure of a laminated body in which both surfaces of an alloy thin strip serving as a magnetic layer are protected by a resin layer via an adhesive.

[0060] Here, the adhesive layer in contact with one surface of the magnetic layer is referred to as a first adhesive layer, and the layer bonded to the magnetic layer via the first adhesive layer is referred to as a first resin layer. In addition, the adhesive layer in contact with the surface of the magnetic layer opposite to the surface having the first adhesive layer is referred to as a second adhesive layer, and the layer bonded to the magnetic layer via the second adhesive layer is referred to as a second resin layer.

[0061] The laminated body constituting the magnetic shielding sheet of the present invention will be described with reference to the drawings.

[0062] Figure 1This is a cross-sectional view schematically showing an example of the magnetic shielding sheet of the present invention. Figure 1 The magnetic shield sheet 10 shown has a first resin layer 12 , a first adhesive layer 14 , a magnetic layer 16 , a second adhesive layer 18 , and a second resin layer 20 in this order.

[0063] The first resin layer 12 , the first adhesive layer 14 , the second adhesive layer 18 , and the second resin layer 20 protect the magnetic layer 16 including a magnetic body from both sides, and can suppress damage to the magnetic layer 16 or peeling from the first resin layer or the second resin layer even when the magnetic shielding sheet 10 is deformed.

[0064] In the magnetic shielding sheet of the present invention, the magnetic layer is a magnetic layer containing a magnetic body with a magnetostriction constant λ of 30 or less and having a thickness of 8 μm to 25 μm, the first resin layer and the second resin layer are resin layers containing a resin with a melting point or sublimation point of 250°C or more and having a thickness of 1 μm to 24 μm, and the first adhesive layer and the second adhesive layer are adhesive layers containing an adhesive with a melting point of 150°C or more and having a thickness of 1 μm to 10 μm, respectively. It is considered that, for example, when the adhesive layer contains a thermosetting resin, even if the adhesive layer is heat-cured, deformation of the adhesive layer and the resin layer can be suppressed, and undesired damage to the magnetic layer can be suppressed. In detail, it is considered that the resin components contained in the resin layer and the adhesive layer themselves have good heat resistance, and the thickness of each layer is thin, thereby achieving the effect of the present invention.

[0065] The details of each layer will be described later.

[0066] In conventionally known magnetic shielding sheets, thermoplastic resin is generally used in the resin layer serving as a protective layer of the magnetic layer, and the thickness of the resin layer often exceeds 30 μm and is often about 50 μm.

[0067] Figure 2 This is a cross-sectional view schematically showing an example of a conventionally known magnetic shielding sheet. Figure 2 The magnetic shielding sheet 22 shown has a first resin layer 24, a first adhesive layer 26, a magnetic layer 28, a second adhesive layer 30 and a second resin layer 32 in sequence. The layer structures are similar, but the first resin layer and the second resin layer are resin layers containing thermoplastic polyethylene with a melting point of 100°C to 150°C and a thickness of more than 30 μm. In addition, because the adhesive contained in the adhesive layer also contains thermoplastic adhesives such as hot-melt adhesives, for example, in a high temperature environment exceeding 100°C, the thermoplastic resin remelts and the protective performance of the magnetic layer may be reduced.

[0068] The magnetic shielding sheet of the present invention is a laminate having a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer and a second resin layer in this order, and its structure is not particularly limited except that the magnetic layer may not necessarily be laminated over the entire surface of the first resin layer and the first adhesive layer in the magnetic shielding sheet, but may be formed only in a local area.

[0069] In a region where the magnetic layer is not disposed, the first adhesive layer and the second adhesive layer may be directly bonded to each other.

[0070] From the viewpoint of magnetic shielding properties, it is preferable that the formation regions of the magnetic layer are arranged regularly.

[0071] The magnetic layer is a preferred form of magnetic shielding sheet, and the following magnetic shielding sheet can be cited: the magnetic layer is a long strip with a width of 30mm to 500mm, the width of the first resin layer, the first adhesive layer, the second adhesive layer and the second resin layer is more than 300mm, and on the surface of the first adhesive layer opposite to the side having the first resin layer, the plurality of magnetic layers are arranged side by side along the long side direction of the long strip.

[0072] Figure 3A This is a schematic structural diagram showing an example of a magnetic shielding sheet in which a plurality of magnetic layers are arranged side by side on the surface of a first resin layer and a first adhesive layer adjacent to the first resin layer. Figure 3A In order to make the structure clear, the layer structure of the magnetic shielding sheet 40 is clearly shown with the side surface as a cross section.

[0073] exist Figure 3A In the perspective view of the magnetic shielding sheet 40 shown in FIG. 1 , the second adhesive layer 18 and the second resin layer 20 are laminated on the surface of the magnetic layer 16 on the opposite side of the side in contact with the first adhesive layer 14. Sometimes, the second adhesive layer 18 and the second resin layer 20 cannot be seen visually due to the thickness of the resin layer 20, etc. Figure 3A In order to clarify the shape and arrangement position of the magnetic layer 16 , the figure is described as a perspective view.

[0074] Regarding the magnetic layers 16 arranged side by side, if there is a gap between adjacent magnetic layers 16, electromagnetic waves may pass through the gap, so the magnetic layers 16 are arranged to overlap partially. Among the magnetic layers 16 arranged side by side, the upper magnetic layer is indicated by a solid line, and the end portion of the magnetic layer arranged to overlap below is indicated by a dotted line.

[0075] exist Figure 3A The arrows in the figure adjacent to the magnetic shielding sheet 40 indicate the longitudinal direction of the magnetic shielding sheet 40 .

[0076] Figure 3B It is a schematic representation of Figure 3A 1 is a schematic cross-sectional view of an example of a cross section of the magnetic shielding sheet taken along line AA shown.

[0077] exist Figure 3B In the cross section of the magnetic shielding sheet 40 on the line AA, that is, the cross section in the width direction, as shown in FIG. Figure 3B As shown in FIG. 1 , the magnetic layer 16 is formed to overlap along the width direction of the magnetic shielding sheet 40. Figure 3B , an example is shown in which the thickness of the first adhesive layer 14 and the second adhesive layer 18 in the region where the magnetic layer 16 overlaps is formed thinner than in the region where the magnetic layer 16 does not overlap, and the thickness of the entire magnetic shielding sheet is substantially uniform.

[0078] Figure 3C is a schematic representation of Figure 3A The cross section of the magnetic shielding sheet on line A-A shown in FIG. Figure 3B A schematic cross-sectional view of another different example.

[0079] exist Figure 3C In the cross section of the magnetic shielding sheet 40 on the line AA shown in FIG. Figure 3C As shown, the magnetic layer 16 is formed in an overlapping manner along the width direction of the magnetic shielding sheet 40. Figure 3C In the illustrated embodiment, in the region where the magnetic layer 16 overlaps, the thickness of the first adhesive layer 14 and the second adhesive layer 18 is also formed to be substantially the same as that of the region where the magnetic layer 16 does not overlap. In the above embodiment, an example is shown in which the adhesion of the overlapping portion is the same as that of the other regions, but in terms of the overall thickness of the magnetic shielding sheet 40, the overlapping portion of the magnetic layer 16 is slightly thicker than the other regions.

[0080] The overlapping portion of the magnetic layer is not limited to the above, and the overlapping width of the magnetic layer 16 and the thickness of the first adhesive layer 14 and the second adhesive layer 18 in the overlapping region of the magnetic layer 16 can be appropriately changed according to the purpose of use of the magnetic shielding sheet.

[0081] When the magnetic layer of the elongated body is laminated on a wider resin layer via an adhesive layer, the width of the magnetic layer of the elongated body can be set to 40 mm to 550 mm, preferably 35 mm to 520 mm, and more preferably 30 mm to 500 mm, from the perspective of productivity and the magnetic shielding properties of the obtained magnetic shielding sheet.

[0082] When a long magnetic layer is laminated on a wider resin layer, the width of the resin layer is preferably 3 times or more, more preferably 5 times or more, and even more preferably 10 times or more of the maximum width of the magnetic layer from the viewpoint of productivity.

[0083] <<Layer structure of magnetic shielding sheet>>

[0084] Next, each layer of the magnetic shielding sheet of the present invention will be described. As described above, the magnetic shielding sheet of the present invention includes a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer, and a second resin layer in this order.

[0085] <First resin layer, second resin layer>

[0086] The first resin layer and the second resin layer function as protective layers for the magnetic layer.

[0087] The first resin layer and the second resin layer are resin layers each containing a resin having a melting point or a sublimation point of 250° C. or higher and having a thickness of 1 μm to 24 μm.

[0088] As resins having a melting point or a sublimation point of 250°C or above, for example, polyimide [melting point: none, heat resistance temperature: 400°C], polyphenylene sulfide (PPS) [melting point: 260°C to 270°C: weighted deflection temperature: 1.8 MPa], aromatic polyamide resin as an aromatic polyamide-based resin [melting point: none (due to sublimation), heat resistance temperature: 400°C], high heat-resistant polyethylene terephthalate (high heat-resistant PET) [melting point: unknown, heat resistance temperature: 250°C], etc., and from the viewpoint of heat resistance and dimensional stability, PPS and aromatic polyamide resins are preferred.

[0089] From the viewpoint of the protectiveness of the magnetic layer, the melting point or sublimation point of the resin (hereinafter also referred to as the specific resin) contained in the first resin layer and the second resin layer is 250° C. or higher, preferably 260° C. or higher, and more preferably 270° C. or higher. The upper limit of the melting point or sublimation point of the specific resin is not particularly limited, but from the viewpoint of processability, the melting point can be set to 300° C. or lower, and the sublimation point can be set to 500° C. or lower.

[0090] In the present invention, the melting point or sublimation point of the resin contained in the resin layer adopts a value generally found in literature.

[0091] The resins contained in the first resin layer and the second resin layer may be the same or different from each other. However, from the viewpoint of stability when a laminate is formed, the same resins are preferred because the thermal behaviors of the first resin layer and the second resin layer can be made consistent.

[0092] The first resin layer and the second resin layer may contain other known components in addition to the above-mentioned specific resins within a range not impairing the effects.

[0093] Examples of other components include organic solvents, surfactants, plasticizers, and colorants.

[0094] The thickness of the first resin layer and the second resin layer is in the range of 1 μm to 24 μm. If the thickness of each resin layer exceeds 24 μm, it is difficult to deform the laminate, which sometimes hinders the magnetic shielding sheet obtained by following the curved surface or the bent surface. In addition, if the thickness is less than 1 μm, the operability of the laminated protective layer is sometimes reduced, and the function of protecting the magnetic layer cannot be fully obtained. By making the thickness of each resin layer within the above range, the protectiveness of the magnetic layer and the suppression of magnetic deformation caused by thermal deformation of the magnetic shielding sheet are good.

[0095] From the viewpoint of the protective property of the magnetic layer, the thickness of each resin layer is preferably 2 μm or more, more preferably 3 μm or more, and further preferably 4 μm or more.

[0096] The upper limit of the thickness of the resin layer is preferably 20 μm or less, more preferably 15 μm or less, and further preferably 10 μm or less, from the viewpoint of flexibility of the magnetic shielding sheet and dimensional stability during heating.

[0097] The thickness of the resin layer can be measured by a contact-type film thickness meter.

[0098] In the present invention, the thickness is measured at five locations of the magnetic shielding sheet, and the arithmetic average of the obtained thicknesses is taken as the thickness of the resin layer.

[0099] The thickness of each layer such as the resin layer and the adhesive layer described below constituting the laminate of the magnetic shielding sheet of the present invention can also be measured by the same method.

[0100] Furthermore, when measuring the thickness of each layer constituting the magnetic shielding sheet having an existing laminated structure, the thickness of each layer can be measured by observing a cut surface obtained by cutting the magnetic shielding sheet perpendicularly to the surface.

[0101] <First adhesive layer, second adhesive layer>

[0102] The first adhesive layer and the second adhesive layer are located between the resin layer as a protective layer of the magnetic layer and the magnetic layer to be described later, and have a function of making the first resin layer and the second resin layer closely adhere to the magnetic layer.

[0103] The first adhesive layer and the second adhesive layer are adhesive layers each containing an adhesive having a melting point of 150° C. or higher and having a thickness of 1 μm to 10 μm.

[0104] The melting point of the adhesive contained in the first adhesive layer and the second adhesive layer (hereinafter also referred to as a specific adhesive) is above 150°C, preferably above 160°C, and more preferably above 170°C. From the viewpoint of heat resistance and dimensional stability, the specific adhesive is preferably a thermosetting adhesive. As a thermosetting adhesive, there can be mentioned a thermosetting adhesive containing a thermosetting resin selected from epoxy resin, unsaturated polyester resin (SMC: Sheet Molding Compound, BMC: Bulk Molding Compound, etc.), urea resin, diallyl phthalate resin, silicone resin, polyimide and polyurethane, among which, from the viewpoint of the ease of forming the adhesive layer and the heat resistance of the obtained adhesive layer, an epoxy resin adhesive is preferred. The adhesive layer can also be formed by transfer molding a resin in a sheet shape. For example, the above-mentioned epoxy resin adhesive is molded into a sheet shape, and the adhesive layer is formed by transfer, thereby easily forming an adhesive layer of uniform thickness.

[0105] The one-component curing epoxy resin adhesive is cured by heating at 150° C. to 200° C., and has better heat resistance after curing than the two-component epoxy resin adhesive.

[0106] The resin contained in the first resin layer and the resin contained in the second resin layer may be the same or different from each other. From the viewpoint of stability when the laminate is made, the thermal behaviors of the first resin layer and the second resin layer are consistent, and deformation caused by thermal stress can be suppressed. Therefore, the resin contained in the first resin layer and the resin contained in the second resin layer are preferably the same resin.

[0107] The thickness of the first adhesive layer and the second adhesive layer are 1 μm to 10 μm, respectively.

[0108] From the viewpoint of ensuring adhesion between the resin layer and the magnetic layer, the thickness of the adhesive layer is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 4 μm or more.

[0109] From the viewpoint of suppressing dimensional change due to heating, the thickness of the adhesive layer needs to be 10 μm or less, and can be 9 μm or less, or even 8 μm.

[0110] For example, when an epoxy resin adhesive is used, by setting the thickness of the adhesive layer to about 10 μm, it is possible to achieve both high levels of adhesiveness and dimensional stability with respect to thermal behavior.

[0111] <Magnetic layer>

[0112] The magnetic layer in the magnetic shielding sheet of the present invention comprises a magnetostriction constant λ of 30×10 ―6The magnetic layer has a thickness of 8 μm to 24 μm and is a magnetic body as follows.

[0113] The magnetic material contained in the magnetic layer has a magnetostriction constant λ of 30×10 ―6 Hereinafter, as the magnetic body, either an amorphous material or a nanocrystalline material can be used.

[0114] From the viewpoint of magnetic properties and strength, the thickness of the magnetic layer is in the range of 8 μm to 25 μm, preferably in the range of 10 μm to 20 μm, and more preferably in the range of 12 μm to 18 μm.

[0115] The magnetostriction constant λ of the magnetic material used in the magnetic layer may be a value from literature or may be measured by the following method.

[0116] <Method for measuring magnetostriction constant λ of magnetic material>

[0117] The magnetostriction constant λ can be measured using a strain sensor.

[0118] As the strain sensor, a strain sensor (model: SKF-40029) manufactured by Kyowa Electric Co., Ltd. can be used.

[0119] The strain sensor is bonded to the magnetic layer with an adhesive.

[0120] As the adhesive, a room temperature curing instant adhesive CC-33A produced by Kyowa Electric Co., Ltd. is used. The adhesive is dripped along the direction of rotation of the magnetic roller (i.e., the long side direction) or in its orthogonal direction (i.e., the width direction) and pressure is applied to spread the adhesive and adhere it to the free surface of the adhesive coating area.

[0121] The obtained laminate of the magnetic body, the adhesive, and the sensor was measured using a strain amplifier (model: PCD-300A) manufactured by Kyowa Electric Co., Ltd. as a strain amplifier.

[0122] The size of the magnetic sample was set to 10 mm×10 mm, and the laminated body was fixed to the center of the electromagnet of the measuring device using a clamp at the center of the electromagnet.

[0123] The measurement was performed by applying a magnetic field having a magnetic field strength of about 5700 Oe to the magnetic body.

[0124] Nanocrystalline materials suitable for magnetic layers can be obtained, for example, by quenching a melt having an alloy composition that can be adjusted to a nanocrystalline structure, such as a Fe-Cu-Nb-(Si, B) system, forming it into a long strip called an amorphous ribbon, and then adjusting it to a nanocrystalline structure by heat treatment. As an example, a nanocrystalline material is a material in which at least 50% of the structure is composed of fine grains with an average grain size of 100 nm or less.

[0125] The nanocrystalline material can be obtained by preparing an amorphous thin ribbon (amorphous ribbon) and then subjecting it to heat treatment at a temperature higher than the crystallization temperature to microcrystallization.

[0126] The magnetic thin strip of amorphous alloy or nanocrystalline alloy as the obtained magnetic layer partially overlaps the ends of the magnetic body in a manner that allows magnetic and electrical coupling, as described above. Figure 3A As shown, multiple lines can be arranged side by side for use.

[0127] The total thickness of the laminate having the first resin layer, the first adhesive layer, the magnetic layer, the second adhesive layer and the second resin layer in this order is preferably in the range of 33 μm to 65 μm, more preferably in the range of 35 μm to 62 μm, and further preferably in the range of 40 μm to 60 μm.

[0128] When the total thickness of the laminate is within the above range, the magnetic shielding sheet of the present invention has good flexibility and processability and exhibits practically sufficient strength.

[0129] <Embodiment of magnetic shielding sheet>

[0130] There is no particular limitation on the embodiment of the magnetic shielding sheet of the present invention.

[0131] The magnetic shielding sheet of the present invention may be continuous in the longitudinal direction, may be a sheet of any shape such as a single sheet or a separate rectangular sheet, or may be a magnetic shielding member obtained by punching a rectangular sheet or a continuous sheet into any shape.

[0132] The magnetic shielding sheet of the present invention may be a rolled magnetic shielding sheet.

[0133] The magnetic shielding sheet in a roll shape by winding the laminated body can be easily stored and transported, and can be unwound and used as needed.

[0134] The magnetic shielding sheet stored in a roll and unwound as needed can be cut into an appropriate size for use, or can be used for punching.

[0135] Furthermore, the magnetic shielding sheet of the present invention may be a magnetic shielding member obtained by punching the above-mentioned laminated body into any shape.

[0136] By punching the laminated body, a magnetic shield member of any shape composed of magnetic shield sheets can be obtained, and can be easily incorporated into various devices.

[0137] Examples of uses of the magnetic shield member punched into an arbitrary shape include use in noise suppression for cameras, medical equipment having image processing, and the like.

[0138] <Preferred physical properties of magnetic shielding sheet>

[0139] The first adhesive layer and the second adhesive layer contain a thermosetting adhesive.

[0140] When A% is defined as the area change rate of the first resin layer before and after heating to a temperature at which the thermosetting adhesive is cured, and B μm is defined as the thickness of the first resin layer, the product of A and B is preferably 30%·μm or less.

[0141] The second resin layer also preferably has the same physical properties as those of the first resin layer.

[0142] The area change rate before and after heating at a temperature at which the thermosetting adhesive is cured is measured by the following method.

[0143] (Measurement method of area change rate)

[0144] According to JIS C 2151:2019 and ASTM DD1204, the resin film constituting the above-mentioned first resin layer is cut into a size of 100 mm×100 mm to prepare a sample. In a heat treatment furnace, according to the curing temperature of the above-mentioned thermosetting adhesive, the obtained resin film sample is heated under the conditions of 200°C×10 min or 150°C×30 min. The thermal shrinkage rate of the resin film in the width direction and the length direction before and after heating is measured by the following method, the area is calculated using the product of the obtained width and length, and the area change rate is measured by the following formula (a).

[0145] The second resin layer was also measured under the same conditions as those for the first resin layer.

[0146] Area change rate (%) = [area of ​​the resin film before heating - area of ​​the resin film after heating] / area of ​​the resin film before heating ... formula (a)

[0147] -Method for measuring thermal shrinkage-

[0148] (1) The dimensions of the test piece in the width direction and the length direction before heating are measured respectively.

[0149] (2) The test piece is placed in a hot air circulation thermostatic chamber and is hung in a loaded state at a time and temperature corresponding to the conditions of the raw material of the resin film.

[0150] Here, as described above, the load may be appropriately selected according to the conditions under which the resin film is suspended in a state where deformation of the resin film is suppressed.

[0151] (3) After heating, the specimen is cooled to room temperature, and then the dimensions of the specimen in the width direction and the length direction after the heating treatment are measured for the same portion as the specimen before heating.

[0152] (4) Using the obtained value, the heat shrinkage ratio is calculated according to the following formula (b).

[0153] Thermal shrinkage (dimensional change) (%) = 100 × (Lo-L) / Lo ... formula (b)

[0154] In the formula (b), Lo represents the size of the test piece before the heating test, and L represents the size of the test piece after the heating treatment.

[0155] Here, for example, when the thermosetting adhesive is aramid, heating may be performed at 200° C. for 10 min, and when it is another thermosetting adhesive such as epoxy resin, heating may be performed at 150° C. for 30 min.

[0156] According to the research of the inventors of the present invention, it was found that in the stability of the magnetic permeability of the magnetic shielding sheet, the heat resistance of the resin contained in the resin layer and the adhesive layer is important. In addition, the dimensional stability of each resin layer and each adhesive layer under thermal conditions such as heating and cooling is important. In addition to the type of resin, the thickness of each layer also has an impact.

[0157] According to the above-mentioned measuring method, if the product of the area change rate of the first resin layer and the second resin layer before and after heating and the thickness of the first resin layer and the second resin layer is 30%·μm or less, respectively, it is possible to effectively suppress the undesirable deformation of the magnetic layer in the magnetic shielding sheet before and after heating. In addition, the thickness of the first resin layer and the second resin layer refers to the thickness of the single resin layer of each of the first resin layer and the second resin layer.

[0158] <Method for manufacturing magnetic shielding sheet>

[0159] A known method can be applied to the method of manufacturing the magnetic shielding sheet.

[0160] The magnetic shielding sheet of the present invention can be produced by the production method and the production apparatus described in Japanese Patent Application Laid-Open No. 2007-43077, for example.

[0161] Figure 4 This is a perspective view showing an example of the main part of a manufacturing apparatus capable of manufacturing the magnetic shielding sheet of the present invention.

[0162] Figure 4 The manufacturing device shown is mainly composed of a heating roller 2, crimping rollers 8a, 8b, 8c arranged around it, and a roller 5 for winding the laminated magnetic shielding sheet. The crimping rollers 8a, 8b, 8c have resin rollers 1a, 1b for conveying the resin layer, thin strip rings 3a, 3b for conveying the magnetic layer, and are used to crimp the magnetic layer and the resin layer.

[0163] exist Figure 4 In the example, all rotation axes are arranged parallel.

[0164] exist Figure 4 In the process, a resin film 6a to be a first resin layer is unwound from the resin roller 1a toward the heating roller 2. An adhesive to form an adhesive layer is applied to one side of the resin film.

[0165] On the resin film 6a having an uncured adhesive layer on one side, amorphous alloy thin strips 7a and 7b forming a magnetic layer are fed from the thin strip loops 3a and 3b at the same speed as the resin film, for example, 3.0×10 6 ~1.2×10 7 The film is unwound with a tension of (Pa) and arranged in parallel on the heating roller 2.

[0166] In addition, it can also be that: the amorphous alloy thin strip forming the magnetic layer is drawn out from a plurality of unwinding rollers arranged at different heights in a magnetically and electrically coupled manner, the amorphous alloy thin strip is drawn out in a manner that the contact surface with the heating roller for heating is all facing one side, and is arranged side by side in a manner that the ends overlap.

[0167] The amorphous alloy thin strip is drawn out from each roller at the same speed, and after coming into contact with the circumference of the heating roller 2, it is directly pressed against the resin film 6a having an adhesive layer by the pressing rollers 8a and 8b.

[0168] More specifically, for example, the amorphous alloy strip 7a may be pressed onto the resin film at a predetermined interval and directly pressed by a pressing roller 8a, and then the portion not covered by the amorphous alloy strip 7a may be covered by the amorphous alloy strip 7b and directly pressed by a pressing roller 8b.

[0169] The amorphous alloy thin strip is brought into contact with the resin film and pressed together by a heating roller and a pressure roller.

[0170] Next, a resin film 6b forming a second resin layer is unwound from a resin roller 1b on the upper layer of the surface covered by the amorphous alloy thin strips 7a and 7b. An adhesive constituting a second adhesive layer is applied to the resin film 6b. The resin film 6b is pressed against the amorphous alloy thin strips 7a and 7b by a pressing roller 8c, thereby manufacturing a laminated body of the resin film 6a forming a first resin layer and a first adhesive layer, the amorphous alloy thin strips 7a and 7b as magnetic layers, and the resin film 6b forming a second adhesive layer and a second resin layer, i.e., a magnetic shielding sheet 9.

[0171] The obtained magnetic shielding sheet was wound around a core material in the same direction as the bending direction of the amorphous alloy thin strip in the initial roll, thereby obtaining a magnetic shielding sheet roll.

[0172] The magnetic shielding sheet may be transported after being wound up by the roller 5 , or may be cut without being wound up by the roller 5 , and stored and transported in the form of overlapping rectangular sheets.

[0173] When the adhesive layer contains a thermosetting adhesive, the adhesive layer may be cured by heat treatment after the formation of the laminate and before winding or cutting.

[0174] The magnetic shielding sheet of the present invention has the above structure, so it can effectively protect the magnetic layer and suppress the undesired degradation of the magnetic layer caused by heat treatment. In addition, the AC specific magnetic permeability μˊ of the magnetic shielding sheet of the present invention shows a practically sufficient value and also has the advantage of suppressing the change over time.

[0175] Example

[0176] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to the following examples.

[0177] <Example 1>

[0178] First, a single-roll cast alloy thin strip FT-3 (manufactured by Bomarichuang Co., Ltd., magnetostriction constant: λ < 1 × 10 -6 ) with a width of 50 mm is used as an alloy thin strip for the magnetic layer.

[0179] As the adhesive layer, a 4.4 μm thick aramid film (melting point: 278° C., manufactured by Toray Industries, Ltd.) was prepared as a resin layer bonded with epoxy resin (heat resistant temperature: 200° C., manufactured by Toray Industries, Ltd.). The adhesive was applied in an amount to give a thickness of 10 μm after curing.

[0180] In order to install the FT-3 tape in the magnetic shield lamination device, a core with a length of 250 m was prepared. When the core was prepared, the roll surface of the nanocrystalline material was wound on the winding core in the direction of becoming the inner circumference side.

[0181] Here, the roll surface of the nano-crystalline material refers to the surface on the side in contact with the casting roll for producing the strip of nano-crystalline material cast by the single roll method.

[0182] After the core was produced, the core was removed from the winding core and heat treated at 590° C. for 1 hour to produce an FT-3 nanocrystalline material core, which was used as the magnetic layer.

[0183] Next, in order to heat-compress the magnetic layer to produce a magnetic shielding sheet, the FT-3 nanocrystalline material core and the aramid film with adhesive prepared above were placed on a laminating device.

[0184] The laminating device uses a Figure 4 The partial structure shown is a manufacturing device described in Japanese Patent Application Laid-Open No. 2007-43077.

[0185] Using this manufacturing device, the nanocrystalline material FT-3M as the magnetic layer, the aromatic polyamide film as the first resin layer formed by a sheet-like epoxy resin bonded as the first adhesive layer as a protective resin film, and the aromatic polyamide film as the second resin layer formed by a sheet-like epoxy resin bonded as the second adhesive layer and a sheet-like epoxy resin bonded together are heated and pre-bonded by a pressing roller under the manufacturing conditions of a heating roller temperature of 60°C and a line speed of 1m / min.

[0186] At this stage, the adhesive is not crosslinked and cured. In order to roll the laminated body that has been pre-pressed by heating into a long strip, it is continuously wound on a winding core. The winding core is made of a paper tube in consideration of heat resistance.

[0187] Next, in order to crosslink and cure the uncured epoxy adhesive to form an adhesive layer, a heat curing treatment was performed in a heat treatment furnace. The heat treatment conditions were set to a temperature of 170° C. and a treatment time of 2 hours.

[0188] The magnetic shielding sheet of Example 1 has the above Figure 1 The layer structure shown.

[0189] After the heat treatment furnace is cooled to room temperature (25° C.), a first resin layer 12, a cured first adhesive layer 14, a magnetic layer 16, a cured second adhesive layer 18, and a second resin layer 20 are obtained. Figure 1 A cross section of the magnetic shielding sheet of Example 1 is shown.

[0190] <Comparative Example 1>

[0191] A polyethylene terephthalate film (PET: melting point: undisclosed, manufactured by Kurabo Co., Ltd.) with a thickness of 25 μm was used to form the resin layer, and a polyolefin-based adhesive (melting point 90° C., manufactured by Kurabo Co., Ltd.) with a thickness of 25 μm was used to form the resin layer. Although not disclosed in the catalog value, the heat resistance temperature of a general PET film is lower than 200° C.

[0192] The laminate was heated and pressure-bonded by pressure bonding rollers under production conditions of a heating roller temperature of 110° C. and a line speed of 2.5 m / min in a laminating device.

[0193] A magnetic shielding sheet of Comparative Example 1 was obtained in the same manner as in Example 1 except that the heat curing treatment described in Example 1 was not performed.

[0194] Table 1 shows the material structures of the magnetic shields of Example 1 and Comparative Example 1 and the thickness of each layer.

[0195] Table 1

[0196]

[0197] As shown in Table 1, it can be seen that the magnetic shielding sheet of Example 1 has a thickness of half or less than that of the magnetic shielding sheet of Comparative Example 1, and can be miniaturized.

[0198] <Evaluation>

[0199] <1. Evaluation of heat resistance appearance>

[0200] The heat resistance of the magnetic shielding sheets of Example 1 and Comparative Example 1 was evaluated, and the appearance before and after the heat resistance test was mainly evaluated.

[0201] This evaluation was conducted by a high storage reliability test at 130°C for 1000 hours. Specifically, the magnetic shielding sheets of Example 1 and Comparative Example 1 were placed in a thermostatic chamber and heated at 130°C for 1000 hours, and the overall appearance changes of the magnetic shielding sheets and the appearance of each layer were observed in detail for evaluation.

[0202] Figure 5A This is a partially enlarged view of a photograph showing the change in appearance of the magnetic shielding sheet of Example 1 after the high storage reliability test. Figure 5B This is a partially enlarged view of a photograph showing changes in the appearance of the magnetic shielding sheet of Comparative Example 1 after the high storage reliability test.

[0203] like Figure 5A As shown, in the magnetic shielding sheet of Example 1, discoloration of the adhesive due to high temperature was observed in the appearance after the test, but the uniformity of the laminate was maintained as a whole, and no damage to the nanocrystalline material as the magnetic layer was observed.

[0204] In contrast, Figure 5B As shown, in the magnetic shielding sheet of Comparative Example 1, the overall appearance is observed to be non-uniform, and the nanocrystalline material as the magnetic layer at the end is exposed due to cracking of the magnetic layer and deformation caused by shrinkage of the PET film as the resin layer, resulting in shedding of the nanocrystalline material. Figure 5B The solid arrows in the figure indicate cracks in the magnetic layer, and the dotted arrows indicate the locations where the magnetic layer has fallen off at the ends.

[0205] <2. Magnetic permeability evaluation>

[0206] The change in the maximum magnetic permeability (μm) of the magnetic shielding sheet of Example 1 and the magnetic shielding sheet of Comparative Example 1 during the high storage reliability test was measured.

[0207] exist Figure 6 2 is a graph showing the elapse of heating time and changes in maximum magnetic permeability. Figure 6 The horizontal axis represents the elapsed time after the start of heating at 130° C., and the vertical axis represents the maximum magnetic permeability.

[0208] The maximum magnetic permeability evaluation method is as follows.

[0209] (Evaluation method of maximum magnetic permeability)

[0210] The maximum magnetic permeability (μm) was measured using a DC magnetization characteristic measuring device manufactured by Metron Technology Laboratory, and the measurement was performed on a sample cut into 15 mm×200 mm using a single-plate magnetic measurement frame.

[0211] like Figure 6 As shown in the graph, even after 1000 hours, the maximum magnetic permeability μm of the magnetic shielding sheet of Example 1 was the same as that before the start of the test, and no significant change in the maximum magnetic permeability was observed in the test under heating conditions.

[0212] In contrast, it is found that the maximum magnetic permeability μm of the magnetic shielding sheet of Comparative Example 1 significantly decreases within 100 hours after the start of the heating test. The decrease in the maximum magnetic permeability is believed to be due to Figure 5B The effect of the nanocrystalline material degradation on the appearance of the magnetic layer is shown.

[0213] The test results show that the magnetic shielding sheet of Example 1 is superior to the magnetic shielding sheet of Comparative Example 1 in terms of heat resistance, appearance, and performance.

[0214] <Measurement of magnetic permeability based on frequency>

[0215] The magnetic permeabilities (μˊ) of the magnetic shielding sheet of Example 1 and the magnetic shielding sheet of Comparative Example 1 were measured at frequencies of 1 kHz and 10 kHz and compared.

[0216] The magnetic permeability μˊ was measured using an impedance analyzer model 4194A manufactured by HEWLET PACKARD. Under the conditions of 1 sample layer, 10 winding turns, and an OSC level of 0.5 V, the inductance L was measured and calculated using the following formula.

[0217] μˊ=(L×average magnetic path length) / (μ0×effective cross-sectional area)

[0218] The test sample is a magnetic shielding sheet punched into an outer diameter of inner diameter Made in the shape of a ring.

[0219] exist Figure 7 The measurement results are shown in .

[0220] It is found that the magnetic shielding sheet of Example 1 has a higher magnetic permeability μˊ than that of Comparative Example 1 at practically common frequencies of 1 kHz and 10 kHz.

[0221] <Example 2>

[0222] In Example 1, a magnetic shielding sheet of Example 2 was obtained by the same method as in Example 1 except that the thickness of the first resin layer and the second resin layer were changed to 12 μm, respectively.

[0223] <Comparative Example 2>

[0224] In Example 1, a magnetic shielding sheet of Comparative Example 2 was obtained by the same method as in Example 1 except that polyphenylene sulfide (PPS) resin (melting point: 260° C. to 270° C., manufactured by Toray Industries, Inc.) was used for the first resin layer and the second resin layer and the thickness was changed to 25 μm.

[0225] Table 2 shows the material structures of the magnetic shields of Example 2 and Reference Example and the thickness of each layer.

[0226] Table 2

[0227]

[0228] <Measurement of magnetic permeability based on frequency>

[0229] Similar to the magnetic shielding sheet of Example 2 and the magnetic shielding sheet of Comparative Example 2, the magnetic permeabilities (μ′) of the magnetic shielding sheet of Example 2 and the magnetic shielding sheet of Comparative Example 2 were measured at frequencies of 1 kHz and 10 kHz and compared.

[0230] exist Figure 8 The results are shown in .

[0231] according to Figure 7 and Figure 8It can be seen that the frequencies of 1 kHz and 10 kHz of Examples 1 and 2 and Comparative Examples 1 and 2 are as follows, and the magnetic shielding sheet of the Example has higher magnetic permeability than the magnetic shielding sheet of the Comparative Example, and exhibits good performance.

[0232] Magnetic permeability of Example 1 (1KHz: 73221.6μ'), (10KHz: 64423.7μ')

[0233] Magnetic permeability of Comparative Example 1 (1KHz: 54482.7μ'), (10KHz: 42962.9μ')

[0234] Magnetic permeability of Example 2 (1KHz: 60866.1μ'), (10KHz: 56930.9μ')

[0235] Magnetic permeability of Comparative Example 2 (1KHz: 56605.7μ'), (10KHz: 43734.6μ')

[0236] The above evaluation results show that the heat resistance and thickness of the resin layer that functions as a protective layer for the magnetic layer affect the performance of the magnetic shielding sheet. In other words, the dimensional stability of each resin layer before and after heating affects the protective performance of the magnetic layer.

[0237] The resin film constituting the resin layer has different thermal expansion and thermal contraction properties when heated depending on the material and thickness of the resin, which affects the protective property of the magnetic layer.

[0238] By suppressing the product of the area change rate of each resin film after the heat treatment relative to that before the heat treatment and the thickness of the resin layer within a predetermined range, the magnetic permeability of the magnetic shielding sheet can be maintained at a high level.

[0239] For verification, the relationship between the product of the area change rate of each resin film after heating treatment relative to that before heating treatment and the thickness of the resin layer and the magnetic permeability μˊ of the obtained magnetic shielding sheet was measured. Fig. 9 The results are shown in .

[0240] Fig. 9 The ● mark shown indicates the results of Example 1, Example 2, Comparative Example 1, and Comparative Example 2 from the left.

[0241] For example, in the aromatic polyamide resin (thickness: 4.4 μm) used in Example 1, the area change rate measured under the following conditions was 0.997%, 0.997×4.4=4.39 (%·μm), achieving 30%·μm or less, and good results were also obtained in the heat resistance evaluation.

[0242] <The product of the area change rate of the magnetic shielding sheet and the thickness of the resin sheet, and the maximum magnetic permeability at a frequency of 10 kHz>

[0243] In the magnetic shielding sheet, the area change rate of the first resin layer and the second resin layer measured under the following conditions is defined as A%, and the thickness of the first resin layer and the second resin layer is defined as Bμm, and the product of A and B (%·μm) and the maximum magnetic permeability are measured. Figure 6 The results are shown in .

[0244] (Measurement method of area change rate)

[0245] The resin film constituting the above-mentioned first resin layer and the above-mentioned second resin layer is cut into a size of 100mm×100mm to prepare a sample. In a heat treatment furnace, if it is an aromatic polyamide resin corresponding to the curing temperature of the thermosetting adhesive, the obtained resin film sample is heated at 200°C for 10 minutes. If it is other adhesives, the obtained resin film sample is heated at 150°C for 30 minutes. The area of ​​the resin film before and after heating is measured, and the area change rate is calculated by the following formula (a).

[0246] Area change rate (%) = [area of ​​the resin film before heating - area of ​​the resin film after heating] / area of ​​the resin film before heating ... formula (a)

[0247] -Method for measuring thermal shrinkage-

[0248] (1) The dimensions of the test piece in the width direction and the length direction before heating are measured respectively.

[0249] (2) The test piece is placed in a hot air circulation thermostatic chamber and is suspended under load at a time and temperature corresponding to the material of the resin film.

[0250] (3) After heating, the test piece is cooled to room temperature, and then the length of the test piece after the heating treatment is measured for the same portion as the test piece before heating measured previously.

[0251] (4) Using the obtained value, the heat shrinkage ratio is calculated according to the following formula (b).

[0252] Thermal shrinkage (dimensional change) (%) = 100 × (Lo-L) / Lo ... formula (b)

[0253] In the formula (b), Lo represents the size of the test piece before the heating test, and L represents the size of the test piece after the heating treatment.

[0254] As described above, the load applied during suspension is adjusted to a load that allows the resin film to be suspended without being deformed.

[0255] like Fig. 9As shown, it can be seen that if the product of A and B (%·μm) is 30%·μm or less, the maximum magnetic permeability that does not cause any practical problems is exhibited at a frequency of 10 kHz.

[0256] That is, it was confirmed that a magnetic shielding sheet having a high magnetic permeability can be obtained by reducing the area change rate of the resin layer itself or the laminate and the thickness of the resin layer.

Claims

1. A magnetic shielding sheet, characterized in that: The magnetic shielding sheet is a laminated body having a first resin layer, a first adhesive layer, a magnetic layer, a second adhesive layer and a second resin layer in this order. The magnetic layer comprises a magnetostriction constant λ of 30×10 -6 The following magnetic body and the magnetic layer having a thickness of 8 μm to 25 μm, The first resin layer and the second resin layer are resin layers each containing a resin having a melting point or a sublimation point of 250° C. or higher and having a thickness of 1 μm to 24 μm. The first adhesive layer and the second adhesive layer are adhesive layers each containing an adhesive having a melting point of 150° C. or higher and having a thickness of 1 μm to 10 μm.

2. The magnetic shielding sheet according to claim 1, characterized in that: The magnetic layer is a long strip with a width of 30 mm to 500 mm. The width of the first resin layer, the first adhesive layer, the second adhesive layer and the second resin layer is 300 mm or more. On the surface of the first adhesive layer opposite to the side having the first resin layer, a plurality of the magnetic layers are arranged side by side along the longitudinal direction of the elongated body.

3. The magnetic shielding sheet according to claim 1 or claim 2, characterized in that: The total thickness of the laminate is 33 μm to 65 μm.

4. The magnetic shielding sheet according to claim 1 or claim 2, characterized in that: The magnetic shielding sheet is in a wound roll shape.

5. The magnetic shielding sheet according to claim 1, characterized in that: The magnetic shielding sheet is a magnetic shielding member obtained by punching the laminated body into an arbitrary shape.

6. The magnetic shielding sheet according to claim 1 or 2, characterized in that: The first adhesive layer and the second adhesive layer contain a thermosetting adhesive, In at least one of the first resin layer and the second resin layer, when the area change rate before and after heating at a temperature at which the thermosetting adhesive is cured is A%, and when the thickness of the first resin layer and the second resin layer is B μm, The product of A and B is less than 30%·μm, Method for determining area change rate: According to JIS C 2151:2019 and ASTM DD1204, the resin film constituting the first resin layer and the second resin layer is cut into a size of 100 mm×100 mm to prepare a sample. The obtained resin film sample is heated in a heat treatment furnace under the conditions of 200°C×10 min or 150°C×30 min according to the curing temperature of the thermosetting adhesive. The heat shrinkage rate of the resin film in the width direction and the length direction before and after heating is measured by the following method. The area is calculated using the product of the obtained width and length, and the area change rate is measured by the following formula (a). Area change rate % = absolute value of [area of ​​the resin film before heating - area of ​​the resin film after heating] / area of ​​the resin film before heating ... formula (a) Thermal shrinkage determination method: (1) Measure the dimensions of the test piece in the width direction and the length direction before heating; (2) placing the test piece in a hot air circulation thermostatic bath and suspending it in a loaded state at a time and temperature corresponding to the raw material of the resin film; (3) After heating, the test piece is cooled to room temperature, and then the length of the test piece after the heating treatment is measured for the same portion as the test piece before heating; (4) Using the obtained value, the heat shrinkage ratio is calculated according to the following formula (b): Thermal shrinkage, i.e., dimensional change rate (%) = 100 × (Lo-L) / Lo…Formula (b) In the formula (b), Lo represents the size of the test piece before the heating test, and L represents the size of the test piece after the heating treatment.

Citation Information

Patent Citations

  • Magnetic shield material and its manufacturing device

    JP2007043077A

  • Magnetic shield member

    JP2007317769A